Need for a digital preservation model based on the administration of digital objects and organizational infrastructure - Molina-Granja, Fernando; Narváez, Estela; Buñay, Pamela; López Ramos, Milton; Reina, Diego (International Journal of Engineering and Technology, 2020)
Public entities or institutions that have the responsibility of keeping long-term data, base their processes on digital preservation, involving the application of information technology and activities in the field of information sciences. The digital preservation has historical implications, it has a direct effect on the cultural heritage, because, without information (digital or not) that is guarded, there is no inheritance or culture, but without technology that allows the preservation or recovery of such information, neither would it be, Thus, the research question is posed as: What technical and legal characteristics are necessary to have an adaptive digital preservation model based on aspects of digital object management and organizational infrastructure, to ensure accessibility of information in the long term in public institutions of Ecuador ?, determining through an evaluation of NESTOR trust repositories and Ecuadorian legislation, that it is necessary to create an adaptive digital Preservation model.Â Â Â